ICT and Economic Growth Nexus: Case of Central Asian Countries - Tursun Shodiev; Bakhodir Turayey; Kamoliddin Shodiyev (Universitas Muhammadiyah Sidoarjo, 2021)
The Government of Uzbekistan declared the year of 2020 as “The Year of Science, Education and Development of the Digital Economy” and is implementing the State Program, aiming at to liberalize the economy, improve market related incentives, encourage private enterprises, to reduce the role of the public sector by introducing ICT and Internet, developing digital economy. In order to understand the causal relationship between ICT investment and economic growth researchers have exert many effort in the world. The results are different: in developed countries the impact of ICT on economic growth is more powerful than in developing countries. This paper aims at finding and measuring causality between Economic growth and ICT development in emerging economies of Central Asian Countries by using panel data over the period of 19 years from 2000 – 2018. The research findings revealed that inflation, trade openness, final consumption expenditure and unemployment impact significantly on GDP per capita in Central Asian countries. The econometric analysis showed that ICT affects to GDP per capita positively and significantly: one percent increase in ICT contributes to GDP per capita 0.1669 percent (fixed broadband subscriptions) and 0.2218 percent (internet usage).Thus we concluded that information and communication technology together with economic indicators are key part of economic development in Central Asian countries. Reduction of inflation and unemployment allow expanding businesses, to create new job places in the digital economy.